(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
The Karnaphuli river, essential for the economy and biodiversity of Bangladesh, faces increasing threat due to the proximity of industries, necessitating regular water quality monitoring to safeguard both environmental and economic interests. Hence, this study investigates the nutrient distribution and physicochemical parameters (pH, temperature, turbidity, dissolved oxygen, and electric conductivity) in relation to the chlorophyll a dynamics in the Karnaphuli river estuary during the monsoon season for evaluating water quality in the river estuary, stretching about 42 kilometres. Surface and deep-water samples have been collected from five different stations. Nutrients, chlorophyll concentration, and dissolved oxygen have been evaluated using a Continuous Flow Autoanalyzer, spectrophotometer, and DO kit, respectively, while electric conductivity, temperature, turbidity, and pH have been measured using a CTD tool. Spatial mapping and correlation analysis have been conducted as well. Temperature and pH values didn’t show much fluctuation within the sampling stations falling within the range of 29°C-31°C and 6.5-7.5, respectively. Positive correlation of pH with ammonia at surface water (r=92) indicates that the effluents of ammonia plants are the primary source of pH in river water. TSP plant effluent has been shown to cause turbidity, evident from the positive correlation between phosphate and turbidity both at surface and deep water (r=91). Increase in turbidity (562.1 NTU) resulted in a decrease in dissolved oxygen (3 mg/L), which poses a serious threat to the survival of aquatic life, including fish, in the river downstream. Decreased water quality at river downstream is evident by comparatively low chlorophyll presence of 1.5 μg/L. However, the shallow coastal region in the study area is indicative of a healthy aquatic ecosystem evident by the presence of high productivity indicated by high chlorophyll concentration of 8.9 μg/L, which is due to comparatively low levels of turbidity and also the water condition there met the standard DO for fisheries (>5mg/L). The findings underscore the critical importance of regular water quality monitoring in the Karnaphuli river to safeguard both the environment and economy of Bangladesh, urging collective action to mitigate the escalating threats posed by industrial activities and ensure the long-term sustainability of the river ecosystem. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(1), 2024, P 91-104